Mixité communautaire : cadre juridique d’un nouveau départ pour l’Irlande du Nord - Christian Mailhes (Cahiers du MIMMOC)
Signed on April 10, 1998, the Good Friday Agreement was intended to officialise the end to violence and offer a legal framework with a common aim which would bring together former enemies in a profoundly divided society. The signatories of the Agreement offered Northern Ireland the basis of a new departure. To achieve that, the mutual acceptance of a mixed society was an inevitable step, the only possible path towards the creation of a society based on new terms. What exactly is meant by a mixed society in the Northern Irish context? The term may seem ambiguous for it is both synonymous with division and at the same time allows for possible integration, mixing and recomposition. The complexity of the situation in Northern Ireland leads to many a contradictory aspect.